A study of p53 expression in transitional cell carcinoma of urinary bladder in Erbil governorate - Ali, Salah A.; ------, Bakir Sadeq (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: This study aimed to evaluate p53 protein expression in both normal bladder epithelium and in cases of transitional cell carcinoma (TCC) of urinary bladder by immunohistochemical study and to correlate p53 expression in urothelial cancer with other clinico-pathological parameters. Methods:This is a retrospective and prospective study for sample collection during the period from January 2006-May 2009. The samples studied included 105 formalin fixed, paraffin embedded urinary bladder tissue specimens; they consisted of the following diagnostic categories: chronic non specific cystitis (n=5) and urothelial cancer (n=100). In this study the nuclear p53 protein expression was detected in tissue samples by Dako Cytomation. LSAB + System-HRP staining protocol using monoclonal mouse anti human protein DO-7. Results:None of the chronic non specific cystitis cases showed p53 nuclear immunostaining, while 93% of urothelial cancer specimens examined showed immunopositivity for p53 protein. In this study, a statistically significant correlation was observed between p53 overexpression rate with the tumor grade (p= <0.001) and histological architecture (p= 0.023), but not with other clinico-pathological parameters like age and gender. Conclusion: Results of the present study showed the validity and simplicity of application of immunohistochemistry in determining the status of p53 protein expression. The results suggest that p53 overexpression is strongly associated with the aggressiveness of urothelial cancer.